2017
DOI: 10.1080/14620316.2017.1300512
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest UV-C treatment combined with 1-methylcyclopropene (1-MCP), followed by storage in continuous low-level ethylene atmosphere, improves the quality of tomatoes

Abstract: Mature green tomatoes (Solanum lycopersicum cv Neang Pich) were exposed to 13.6 kJm-2 UV-C or 0.5 μl l −1 1-MCP or combination of 13.6 kJm-2 UV-C and 0.5 μl l −1 1-MCP, with appropriate untreated controls. After treatment, tomatoes were stored in continuous air containing 0.1 μl l −1 ethylene at 20°C and 100% RH. The untreated fruit ripened significantly faster than all other treatments. UV-C treatment alone was able to delay fruit ripening by up to five days longer compared to untreated fruits whilst the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
1
12
0
1
Order By: Relevance
“…Respiration rate was measured by the method described by Pristijono et al (2017a), where 6 oranges from each replicate were allocated into 500 mL hermetic glass jars with a septum in the lid at 20 °C, and headspace gas sample (1 mL) was collected by a syringe after 1 h, and transferred to an ICA40 series low-volume gas analysis system (International Controlled Atmosphere Ltd., Kent, UK). Respiration rate was expressed as µg CO2 kg −1 s −1 .…”
Section: Respiration Ratementioning
confidence: 99%
“…Respiration rate was measured by the method described by Pristijono et al (2017a), where 6 oranges from each replicate were allocated into 500 mL hermetic glass jars with a septum in the lid at 20 °C, and headspace gas sample (1 mL) was collected by a syringe after 1 h, and transferred to an ICA40 series low-volume gas analysis system (International Controlled Atmosphere Ltd., Kent, UK). Respiration rate was expressed as µg CO2 kg −1 s −1 .…”
Section: Respiration Ratementioning
confidence: 99%
“…Green capsicums firmness was measured according to Pristijono et al (2017a), with some slight modifications, where the firmness determined as the maximum force (Lloyd Texture Analyser, Fareman, UK), required to push a 68 mm 2 flat probe into the fruit flesh to a depth of 7 mm. The average of two reading points from each side of the fruit was taken three cm from calyx-end.…”
Section: Fruit Quality Assessmentmentioning
confidence: 99%
“…UV-C treatment has been reported to delay degreening in other horticultural produce such as on broccoli, which showed delayed yellowing for 6 days following exposure to 10 kJ m -2 UV-C treatment (Costa et al 2006). Similarly, after exposure of green tomato fruit to UV-C lights and the results showed that UV-C treatment delayed the ripening of tomatoes by maintaining green colour (Liu et al 2009;Tiecher et al 2013;Pristijono et al 2017a). In addition, Artés-Hernández et al (2009) also reported that UV-C treatment maintained green colour of spinach leaves.…”
Section: Peel Colourmentioning
confidence: 94%
“…Respiration rate was measured by the method described by Pristijono et al (2017a), where 4 limes from each replicate were allocated into 1500 mL hermetic glass jars with a septum in the lid at 20°C, and headspace gas sample (5 mL) was collected by a syringe after 3 h, and transferred to an ICA40 series low-volume gas analysis system (International Controlled Atmosphere Ltd., Kent, UK). Respiration rate was calculated by the Eq.…”
Section: Determination Of Fruits Quality Attributesmentioning
confidence: 99%